(3cJGH GdfhGOQs - (3SYjO Hf GhS Hf KGHJ Hf RjO Hf bjS GdCfUGQj, CHh RjO,J (B215 (3g` s
(3ChdgG (B:s
(3gPG cJGH CHj RjO SYjO Hf ChS Hf KGHJ eeG SeYg ef GdeaVd Hf eMeO GdVHi hef GdeYQH bGd CHh MGJe bGd di CHh RjO eG cGf ajg ef TYQ GdbUjO s
(3BNQgG (B:s
(3hGdcHO ef dMhe GdCHd hGcJMd fe hPcgeG eY GdCcd efgeG CjGekG eJhGdjI RGd GdCde hGddg CYde s
(3HChdgG Jedcs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B92 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B220s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi s
Keywords: (3GddZIs